A methacrylate monomer bearing nitro, aryl, and hydroxyl side groups: Homopolymerization, characterization, dielectric, and thermal degradation behaviors - Biryan, Fatih; Demirelli, Kadir (Wiley-Blackwell, 2016)
2-Hydroxy-3-(4-nitrophenoxy)propyl methacrylate (HNPPMA) monomer was synthesized. The poly(HNPPMA) was prepared by free radical polymerization (FRP) method. The characterization of poly(HNPPMA) was carried out using FT-IR, NMR, differential scanning calorimetry, and GPC techniques. The thermal stability and degradation behavior of this polymer have been studied by using thermogravimetry (TG), GC-MS, NMR, and FT-IR. The results were in comparison to poly[2-hydroxy-3-(1-naphtyloxy)propyl methacrylate] sample with -naphtyloxy side group prepared by the same method in the our previous study. The effect of thermal activation on non-isothermal decomposition kinetics of poly(HNPPMA) was investigated using thermogravimetric analysis according to Flynn-Wall-Ozawa method. The dielectric measurements of poly(HNPPMA) and doped with europium(III)chloride (EuCI3) were investigated by impedance analyzer technique in range of 10-4000 Hz frequency by depending on the alternating current conductivities. The mode of thermal degradation including formation of the main products of poly(HNPPMA) degraded from ambient temperature to 500 degrees C was identified. S degrees, the cold ring fraction (CRF) was collected from room temperature to 500 degrees C. The structure of the degradation products has also been studied depending on the GC-MS analysis. The thermal degradation mechanism for poly(HNPPMA) with radical degradation processes thought to dominate at high temperature was proposed based on GC/MS, NMR, FT-IR, and taking into account the new products and differences in stability. (c) 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43925.
Keywords: dielectric properties; properties and characterization; thermal properties